Relationship between Serum miR-106 and MYL4 Levels and the Prevalence, Risk Stratification, and Prognosis of Atrial Fibrillation - Yanfeng Liu; Haiwen Zhou; Yu Tao; Zhicheng Xu; Hengli Lai (Journal of Immunology Research)
Objective. To analyze the predictive value of serum microRNA-106 (miRNA-106), miR-106, and myosin light chain 4 (MYL4) levels on the prevalence of atrial fibrillation and to explore the relationship between serum miR-106 and MYL4 and the risk stratification and prognosis of atrial fibrillation, thereby providing basis for them to become clinical targets for the treatment of atrial fibrillation in the future. Methods. 300 patients with atrial fibrillation treated in our hospital from May 2017 to March 2019 were selected as the atrial fibrillation group, and 300 healthy people who came to our hospital for physical examination in the same period were selected as the control group. The general data of the subjects in the two groups were collected. The serum miR-106 level of the subjects in the two groups was detected by fluorescence quantitative polymerase chain reaction (PCR), and the level of MYL4 was detected by enzyme-linked immunosorbent assay (ELISA). The expression of miR-106 and MYL4 in the myocardium was observed by immunohistochemistry. The relationship between the levels of serum miR-106 and MYL4 and the prevalence of atrial fibrillation and the score of atrial fibrillation thromboembolism risk stratification scoring system (cha2ds2) was compared between the two groups. The relationship between serum level of miR-106 and prognosis of patients with atrial fibrillation was analyzed. Results. The systolic blood pressure, diastolic blood pressure, total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), and left anterior descending artery (LAD) in the atrial fibrillation group were significantly higher than those in the control group, while HDL-C and left ventricular ejection fraction (LVEF) were significantly lower than those in the control group (P<0.01). The level of serum miR-106 in patients with atrial fibrillation was significantly higher than that in the control group, whereas the level of MYL4 was significantly lower than that in the control group (P<0.01). miR-106 was mainly localized in the cytoplasm, and the positive expression rate of miR-106 was 71.43% (81/115) in patients with atrial fibrillation and 21.74% (25/115) in patients with sinus rhythm. MYL4 was mainly located in the cell membrane and the positive expression rate of MYL4 was 24.35% (28/115) in patients with atrial fibrillation and 64.35% (74/115) in patients with sinus rhythm. With the increase of the severity of atrial fibrillation, the level of serum miR-106 gradually increased and the level of MYL4 gradually decreased, which were statistically significant compared with the control group (P<0.05). With the increase of miR-106 level and the decrease of MYL4 level, the prevalence of atrial fibrillation gradually increased. With the increase of cha2ds2 score, the level of serum miR-106 increased and the level of MYL4 decreased. The survival rate of patients with miR−106≤1.96 was significantly higher than that of patients with miR−106>1.96. The survival rate of patients with MYL4≥0.24 was significantly higher than that of patients with MYL4<0.24. At the same time, TC and LDL-C were included in the analysis. The results showed that the survival rate of patients with TC≤4.5 mmol/L was significantly higher than that of patients with TC>4.5 mmol/L, and that of patients with LDL-C≤2.6 mmol/L was significantly higher than that of patients with LDL-C>2.6 mmol/L. Conclusion. Serum miR-106 and MYL4 levels are closely related to the prevalence of atrial fibrillation, which can reflect the risk of thromboembolism in patients with atrial fibrillation and can be used as a biological indicator to predict the prognosis of patients with atrial fibrillation.